2021
DOI: 10.3389/fpubh.2021.726491
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Characteristics of and Prognostic Factors for COVID-19 Among Hospitalized Patients: Updated Implications From Hubei Province, China

Abstract: Introduction: The roles of some indicators in the prognosis of patients with coronavirus disease-19 (COVID-19) remain unclear and controversial. This study aimed to explore the epidemiologic characteristics of and prognostic factors for COVID-19 to provide updated recommendations for its prevention, diagnosis, and treatment.Methods: For this retrospective study, demographic, epidemiologic, and clinical data were extracted from the medical records of patients admitted to the Maternal and Child Hospital of Hubei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
2
2
0
Order By: Relevance
“…In addition, ALE patients had longer hospital stay, as we demonstrated here in agreement some studies (48) . A multicenter retrospective study with 1765 patients in Hubei province, in China, reported an increased mortality risk in cases of elevated AST (above 34 U/L) (49) , although we did not find it, in line with some other studies (43,15) . In the present study, 23.6% of patients died, and patient aged above 60 years had a higher risk of death (40) These findings are consistent with several studies (14,50,51) including a Brazilian one (45) .…”
Section: Discussionsupporting
confidence: 82%
“…In addition, ALE patients had longer hospital stay, as we demonstrated here in agreement some studies (48) . A multicenter retrospective study with 1765 patients in Hubei province, in China, reported an increased mortality risk in cases of elevated AST (above 34 U/L) (49) , although we did not find it, in line with some other studies (43,15) . In the present study, 23.6% of patients died, and patient aged above 60 years had a higher risk of death (40) These findings are consistent with several studies (14,50,51) including a Brazilian one (45) .…”
Section: Discussionsupporting
confidence: 82%
“…Clinical investigations have found that a low level of albumin was associated with a higher risk of COVID-19 infection [21]. Here we observed that the albumin level in rehabilitated patients were dramatically decreased, especially in elderly group.…”
Section: Discussionsupporting
confidence: 46%
“…Here we observed that the albumin level in rehabilitated patients were dramatically decreased, especially in elderly group. The elevated A/G ratio was reported associated with a poorer prognosis for COVID-19 infection [21]. No signi cant difference in the A/G ratio was observed in rehabilitated patients with mild COVID-19; however, it was signi cant declined when compare the rehabilitated patients with healthy controls in elderlies.…”
Section: Discussionmentioning
confidence: 90%
“…A study in Wuhan, Hubei Province, China, showed that decreased lymphocytes were related to a higher risk of disease severity in male COVID-19 patients with hypertension 38 . However, another study from Hubei province showed that a poorer prognosis was associated with elevated basophil or lymphocyte counts 39 . In our data set, the MO group had increased levels of WBC and neutrophil, lymphocyte, monocyte, eosinophil, and basophil.…”
Section: Discussionmentioning
confidence: 98%